2017
DOI: 10.1002/jsfa.8459
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Capsicum peppers: capsaicinoid content and antioxidant activity

Abstract: Our results suggest that phenolic compounds significantly contribute to the antioxidant activity of the investigated peppers. Also, these data add valued novel information that enhances current knowledge of Brazilian pepper fruits. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 55 publications
9
34
1
6
Order By: Relevance
“…The hierarchical cluster analysis showed the greatest distance between 'Jolokia' and 'Aji Lemon Drop', taking into account both leaf and fruit trials. It can be concluded that capsaicinoids and AsA are responsible for antioxidant activity of highly pungent peppers such as 'Jolokia' under the conditions of our experiment, although the importance of phenolic compounds in the contribution to the total antioxidant activity of peppers, suggested by Bogusz et al [37], could be significant in mildly pungent genotypes such as 'Aji Lemon Drop'. Asnin and Park [38] stated that the capsaicin profile did not directly reflect antioxidant activity, due to the presence of other antioxidant compounds, i.e., phenolics.…”
Section: Stress Parameters Of Chilli Pepper Fruits and Leavescontrasting
confidence: 57%
“…The hierarchical cluster analysis showed the greatest distance between 'Jolokia' and 'Aji Lemon Drop', taking into account both leaf and fruit trials. It can be concluded that capsaicinoids and AsA are responsible for antioxidant activity of highly pungent peppers such as 'Jolokia' under the conditions of our experiment, although the importance of phenolic compounds in the contribution to the total antioxidant activity of peppers, suggested by Bogusz et al [37], could be significant in mildly pungent genotypes such as 'Aji Lemon Drop'. Asnin and Park [38] stated that the capsaicin profile did not directly reflect antioxidant activity, due to the presence of other antioxidant compounds, i.e., phenolics.…”
Section: Stress Parameters Of Chilli Pepper Fruits and Leavescontrasting
confidence: 57%
“…As wild Piquin chili is a natural resource, differences may correspond to polymorphisms in the glabriusculum variety at the biochemical level and technical factors associated with each methodology, in addition to the environment, in which each ecotype grew. In general, concentrations corresponded to on‐off effects of the microclimate of the state of Tamaulipas, which are comparable to variations identified among and within species of Capsicum . In contrast to herbs and spices such as parsley, oregano and cinnamon that are considered specific sources of free radical‐scavengers, values observed in wild population of Piquin chili are considerably low.…”
Section: Discussionsupporting
confidence: 61%
“…The free radical‐scavengers capacity might be attributed to the synergistic effects of several biochemical compounds, as the presence of capsaicinoids may also have influenced the antiradical capability; however, populations with greater pungency did not display a greater free radical‐scavenging capacity. Regarding the fluctuations of the ratio of these two principal capsaicinoids and their concentrations, Bogusz et al . have related these parameters to the phenology of each species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations